Petsamo-Kirkenes Operation : Soviet breakthrough and pursuit in the Arctic, October 1944. - Gebhardt, James F., 1948- (Fort Leavenworth, KS : Combat Studies Institute, US Army Command and General Staff College, 1989)
Primarily using Soviet soldiers, the author has written a comprehensive study of the 1944 Soviet offensive conducted to clear German forces from the approaches to Murmansk. Its focus is at the operational level of war, with emphasis on the peculiar demands of arctic terrain on commanders and soldiers. The paper also used German war diary reports to add clarity and perspective to the Soviet accounts. It describes the employment on arctic terrain of light infantry, infantry, armor, artillery, engineers, logistic support, air power, navel Infantry (Soviet marines), amphibious forces, and special purpose forces. In three weeks of often intense fighting, supported by units of the Northern Fleet, the Red Army inflicted significant personnel and materiel losses on the German force and drove it from Soviet and northern Norwegian territory. This operational account provides the U.S. Army with the opportunity to review the lessons the Soviets have drawn from this arctic battle.